Phenotype-Specific Response of Circulating miRNAs Provides New Biomarkers of Slow or Fast Muscle Damage - Siracusa, Julien; Koulmann, Nathalie; Sourdrille, Antoine; Chapus, Charles; Verret, Catherine; Bourdon, Stéphanie; Goriot, Marie-Emmanuelle; Banzet, Sébastien (Frontiers in Physiology, 2018)
Skeletal muscle is a heterogeneous tissue composed of a continuum of contracting fibers ranging from slow-type to fast-type fibers. Muscle damage is a frequent event and a susceptibility of fast-fibers to exercise-induced damage (EIMD) or statins toxicity has been reported. Biological markers of muscle damage such as creatine kinase (CK) are not fiber-type specific and new biomarkers are needed. Some microRNAs (miRNAs) are specific to the muscle tissue, can be found in the extracellular compartment and can rise in the plasma following muscle damage. Our aim was to identify whether a set of circulating miRNAs can be used as fiber-type specific biomarkers of muscle damage in a model of traumatic (crush) injuries induced either in the slow soleus (SOL) or in the fast extensor digitorum longus (EDL) muscles of rats. A subset of miRNAs composed of miR-1-3p, -133a-3p, -133b-3p, 206-3p, -208b-3p, 378a-3p, -434-3p and -499-5p were measured by RT-PCR in non-injured SOL or EDL muscle and in the plasma of rats 12h after damage induced to SOL or EDL. MiR-133b-3p, -378a-3p and -434-3p were equally expressed both in SOL and EDL muscles. MiR-1-3-p and -133a-3p levels were higher in EDL compared to SOL (1.3 and 1.1 –fold, respectively). Conversely, miR-206-3p, -208b-3p and -499-5p were mainly expressed in SOL compared to EDL (7.4, 35.4 and 10.7 –fold, respectively). In the plasma, miR-1-3p and -133a-3p were elevated following muscle damage compared to a control group, with no difference between SOL and EDL. MiR-133b-3p and -434-3p plasma levels were significantly higher in EDL compared to SOL (1.8 and 2.4 –fold, respectively), while miR-378a-3p rose only in the EDL group. MiR-206-3p levels were elevated in SOL only (4 –fold compared to EDL). Our results show that plasma miR-133b-3p and -434 are fast-fiber specific biomarkers, while miR-206-3p is a robust indicator of slow-fiber damage, opening new perspectives to monitor fiber-type selective muscle damage in research and clinic.